2014
DOI: 10.1080/00014788.2013.867403
|View full text |Cite
|
Sign up to set email alerts
|

The perceived credibility of forward-looking performance disclosures

Abstract: We investigate the credibility of forward-looking performance disclosures (FLPDs) in the narrative sections of annual reports, as perceived by investors. Our proxy for these disclosures is an index of statements about future performance. We find that companies issue more FLPDs when raising debt or conveying bad news in the financial statements. In the presence of these managerial incentives, investor reliance on FLPDs increases with the quality of earnings reported in the audited financial statements. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 104 publications
(152 reference statements)
6
69
1
Order By: Relevance
“…Hossain et al (2005) showed that growth opportunities are positively related to the extent of forward-looking disclosure. In the same way, Athanasakou and Hussainey (2009) showed that growth opportunities measured by book to market value is negatively related to forward-looking information. Hence, high growth companies are more likely to provide additional information to maximise shareholder value in the market.…”
Section: Growth Opportunitiesmentioning
confidence: 71%
See 2 more Smart Citations
“…Hossain et al (2005) showed that growth opportunities are positively related to the extent of forward-looking disclosure. In the same way, Athanasakou and Hussainey (2009) showed that growth opportunities measured by book to market value is negatively related to forward-looking information. Hence, high growth companies are more likely to provide additional information to maximise shareholder value in the market.…”
Section: Growth Opportunitiesmentioning
confidence: 71%
“…The current study employs automated content analysis using computerised software, QSR NVivo 8, to investigate the extent of forward-looking Previous studies that used automated content analysis (e.g., Hussainey et al 2003;Beattie et al, 2004;Aljifri and Hussainey, 2007;Athanasakou and Hussainey, 2009) have employed Nudist software, which performs coding at the sentence level as a unit of code. In the current study coding is performed at the text unit as a unit of analysis.…”
Section: Previous Studies Employing Computerised Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Skinner (1994) found that bad news disclosures generate larger stock price reactions than good news. Athanasakou and Hussainey (2014) showed that narrative reduces market uncertainty about future earnings and increases the credibility of financial statements. Managers pursuing stockholder wealth maximisation will only disclose news likely to increase share prices.…”
Section: The Impact Of Td On Fpmentioning
confidence: 99%
“…is theme presents papers referring to factors concerning audit reports and the impacts that may a ect the clients of the nancial statements. As an example we list the analysis about fair value, as compulsory and voluntary disclosures, adjustments and errors existing in the nancial statements, disclosure of nancial reports in the internet, and presentation of transparency report (Athanasakou & Hussainey, 2014;Carcello & Li, 2013;Chen, Elder, & Hung, 2014;Chi, Dhaliwal, Li, & Lin, 2013;Luypaert & Van Caneghem, 2014). More than doubled, becoming the most identi ed in this area (36.3%) and it appears every year and all publications.…”
Section: Established Themesmentioning
confidence: 99%